Efektivitas Model Pembelajaran Think Talk Write Ditinjau dari Kemampuan Representasi Matematis Siswa - Aghnesia, Aghnesia Rahmy; Caswita, Caswita Caswita; Widyastuti, Widyastuti Widyastuti (FKIP Universitas Lampung, 2017)
The effectiveness learning model of think talk write on students’ mathematical representation skills. This research aimed to find out the effectiveness of cooperative learning Think Talk Write type on students mathematical representation skills. The population of this research was all students of eighth grade in SMP N 1 Kotabumi in academic year of 2018/2019 as many as 244 students which were distriuted into eight classes. The sample of this research were all students of class VIII D as many as 32 students and VIII E as many as 32 students who were selected by cluster random sampling technique. The design which was used in this research was pretest-posttest control group design and the data collecting technique was test. The research data was the increasing score of mathematical representation skills that obtained through an essay test. Based on the result of proportion test and test using 0,05 of significance level, concluded that cooperative learning Think Talk Write type was not effective on students mathematical representation skills.Keyword: effectiveness, mathematical representation, think talk writeDOI: http://dx.doi.org/10.23960/jpmipa/v18i2.pp1-12